Risk Factors Associated with Congenital Anomalies among Children Admitting Surgical Unit in Rapareen Pediatric Teaching Hospital in Erbil City - Chawarwan Saleem Abdullah; Shukir Saleem Hasan (Hawler Medical University, 2023)
Backgrounds and objectives: Congenital anomalies, which can affect how the body operates, are anatomical, functional, or metabolic abnormalities that develop during intrauterine life. The study aimed to identify risk factors associated with congenital anomalies among children who are admitting to the surgical unit at Rapareen Pediatric Teaching Hospital in Erbil city. Methods: descriptive, case-control design was used to conduct this study. This study was conducted in Rapreen Pediatric Teaching Hospital in Erbil from 1st of July to 1st of October 2022. Non- probability purposive sample of 100 mothers with congenital anomalies children and admitted to the Surgical Unit and 100 mothers with other health condition children (control group) at Rapareen Pediatric Teaching Hospital were asked respectfully to participate in the study. Descriptive and frequency, Regression analytics was used for exploring the factors associated with congenital anomalies, Chi-square was used to find out the association between dependent and independent variables, and t-tests were used to identify the differences between case and control groups. Results: the results show that that anemia in pregnancy, previous history of congenital anomalies, family history of congenital anomalies, Pesticide use, living near of mobile station, passive smoke, stress during pregnancy, didn't use folic acid, and drink of coffee during pregnancy had a very high statistical difference between case and control P-value <0.001, while Radiation exposure had a difference between case and control P-value of 0.045. That age of mothers and weight were factors which highly statistical associated with congenital anomalies among children P-value 0.001 and <0.001 respectively, moreover age of father and history of previous abortion were factors behind the congenital anomalies P-value 0.033 and 0.017 respectively.   Conclusions: the study concluded that age of mothers and father, weight, and history of previous abortion were factors behind the congenital anomalies. Primary prevention is most important to reduce the......